HIV Transmembrane Glycoprotein Conserved Domains and Genetic Markers Across HIV-1 and HIV-2 Variants - Valadés-Alcaraz, Ana; Reinosa, Roberto; Holguín, África (Frontiers in Microbiology, 2022)
HIV envelope transmembrane glycoproteins gp41 (HIV-1) and gp36 (HIV-2) present high variability and play a key role in the HIV-host cell membrane’s fusion, as a target for human broadly-neutralizing antibodies (bnAbs) and drugs. Thus, a better knowledge of amino acid (aa) conservation across structural domains and HIV variants can help to identify conserved targets to direct new therapeutic and diagnostic strategies. All available gp41/gp36 nucleotide sequences were downloaded from Los Alamos National Laboratory (LANL) HIV Sequence Database, selecting 17,078 sequences ascribed to HIV-1 and HIV-2 variants with ≥3 sequences. After aligning and translating into aa with MEGAv6.0, an in-house bioinformatics program (EpiMolBio) was used to identify the most conserved aa and the aa changes that were specific for each variant (V-markers) vs. HXB2/BEN (HIV-1/HIV-2) reference sequence. We analyzed the presence of specific aa changes among V-markers affecting infectivity, gp41 structure, function, or resistance to the enfuvirtide viral fusion inhibitor (T-20). We also inferred the consensus sequences per HIV variant, describing in each HIV-1 group (M, N, O, P) the conservation level along the complete gp41 per structural domain and locating in each binding site the anti-gp41 human Abs (bnAbs and non bnAbs) described in LANL. We found 38.3%/59.7% highly conserved aa present in ≥90% of the 16,803/275 gp41/gp36 sequences ascribed to 105/3 HIV-1/HIV-2 variants, with 9%/12.6% of them showing complete conservation across LANL sequences. The fusion peptide, its proximal region, the N-heptad repeat, and the membrane proximal external region were the gp41 domains with ≥84% of conserved aa in the HIV-1 consensus sequence, the target of most Abs. No natural major resistance mutations to T-20 were observed. Our results show, for the first time, a complete conservation study of gp41/gp36 per variant in the largest panel of HIV variants analyzed to date, providing useful information for a more rational design of drugs, vaccines, and molecular detection tests targeting the HIV transmembrane glycoprotein.